Polysemy and apparent polyfunctionality of the Sakhalin Ainu prefixes e- and ko-: Insights on applicativization and aspect - Elia Dal Corso (International Journal of Eurasian Linguistics, 2021)
The present study focuses on the polysemous verbal prefixes e- and ko- of Sakhalin Ainu and proposes their analysis as markers of high transitivity. The author takes a compositional approach to argument structure and event structure in order to account for the main use of e- and ko- as applicative markers as well as for their less common use as markers of resultative-completive and intensive aspect. Ultimately, the analysis shows that the apparent polyfunctionality of e- and ko- arises from two separate applications at the syntax-semantics level of one same underlying function of the prefixes. The author also comments on how the Sakhalin Ainu case fits in with other cases of valence-aspect conceptual overlapping cross-linguistically and on the implications of his findings for Ainu studies specifically.